Local IPOs and household stock market participation - Jiang, Feng; Lowry, Michelle; Qian, Yiming (Review of Finance, 2024)
The decrease in companies going public has received widespread attention, and the associated costs are widely debated. We document that high local initial public offering (IPO) activity leads to increases in stock market participation of 5–6 percent. This is striking, given that such participation represents a key factor toward building wealth. Local IPOs increase both households’ propensity to own stock and their percent equity holdings. The attention channel drives effects: local IPOs attract attention to the market, through increased information production and publicity. The wealth channel has little influence, consistent with local IPOs not generating wealth shocks for most households.